Two distinct coagulase-dependent barriers protect Staphylococcus aureus from neutrophils in a three dimensional in vitro infection model. - Christoph Guggenberger; Christiane Wolz; Julie A Morrissey; Jürgen Heesemann (PLoS Pathogens, 2012)
Staphylococcus aureus is a pyogenic abscess-forming facultative pathogenic microorganism expressing a large set of virulence-associated factors. Among these, secreted proteins with binding capacity to plasma proteins (e.g. fibrinogen binding proteins Eap and Emp) and prothrombin activators such as Coagulase (Coa) and vWbp are involved in abscess formation. By using a three-dimensional collagen gel (3D-CoG) supplemented with fibrinogen (Fib) we studied the growth behavior of S. aureus strain Newman and a set of mutants as well as their interaction with mouse neutrophils by real-time confocal microscopy. In 3D-CoG/Fib, S. aureus forms microcolonies which are surrounded by an inner pseudocapsule and an extended outer dense microcolony-associated meshwork (MAM) containing fibrin. Coa is involved in formation of the pseudocapsule whereas MAM formation depends on vWbp. Moreover, agr-dependent dispersal of late stage microcolonies could be observed. Furthermore, we demonstrate that the pseudocapsule and the MAM act as mechanical barriers against neutrophils attracted to the microcolony. The thrombin inhibitor argatroban is able to prevent formation of both pseudocapsule and MAM and supports access of neutrophils to staphylococci. Taken together, this model can simulate specific stages of S. aureus abscess formation by temporal dissection of bacterial growth and recruitment of immune cells. It can complement established animal infection models in the development of new treatment options.